THE EFFECTIVENESS OF PHONOLOGICAL AWARENESS AS THE ACTION RESEARCH IN SPEAKING - Fithrah Auliya Ansar (SELTICS, 2019)
Mastering English for the students is very important since the skill can be the key to study other knowledge. Speaking is considered as a major skill to be mastered by students in terms of communication. When students attempt to speak, they try to match the sounds with known letters. Due to improving students' speaking English competence, the writer applied phonological awareness in the learning process in order to find the its effectiveness in Speaking. An important link in developing phonological awareness was to encourage students to use invented spelling. The writer formulated a hypothesis as follows: Is there any significant effect of phonological awareness on speaking performance at the fifth-grade students of English Education Department of UIN Raden Intan Lampung. This research was intended to find out the empirical evidence of students’ achievement in speaking performance by using phonological awareness training. This research was Classroom Action Research. The population of the research was all students of English Department in 5th semester. The implementation of speaking skills run well and smoothly by applying the use of phonological awareness methods in learning Process. Initially, it found difficultiesin Cycle I and had not run optimally because lecturers and students were not used to it and had not yet experienced it, but after applying it twice, the meeting in Cycle II used phonological awareness method could run smoothly. The actions taken in the use of the phonological awareness method in each round were carried out by students with enthusiasm and full of motivation. Activities and student involvement in learning activities have begun to appear. Learning progressed smoothly with the maximum result seen in Cycle III, students had understood the benefits of the phonological awareness method in learning. Individual participation and student enthusiasm were also increasing. Key words: Phonological Awareness, Speaking Performance, CAR Mastering English for the students is very important since the skill can be the key to study other knowledge. Speaking is considered as a major skill to be mastered by students in terms of communication. When students attempt to speak, they try to match the sounds with known letters. Due to improving students' speaking English competence, the writer applied phonological awareness in the learning process in order to find the its effectiveness in Speaking. An important link in developing phonological awareness was to encourage students to use invented spelling. The writer formulated a hypothesis as follows: Is there any significant effect of phonological awareness on speaking performance at the fifth-grade students of English Education Department of UIN Raden Intan Lampung. This research was intended to find out the empirical evidence of students’ achievement in speaking performance by using phonological awareness training. This research was Classroom Action Research. The population of the research was all students of English Department in the 5th semester. The implementation of speaking skills runs well and smoothly by applying the use of phonological awareness methods in the learning Process. Initially, it found difficulties in Cycle I and had not run optimally because lecturers and students were not used to it and had not yet experienced it, but after applying it twice, the meeting in Cycle II used phonological awareness method could run smoothly. The actions taken in the use of the phonological awareness method in each round were carried out by students with enthusiasm and full of motivation. Activities and student involvement in learning activities have begun to appear. Learning progressed smoothly with the maximum result seen in Cycle III, students had understood the benefits of the phonological awareness method in learning. Individual participation and student enthusiasm were also increasing. Key words: Phonological Awareness, Speaking Performance, CAR